Effect of Roofing Materials on Hemato-Biochemical, Hormonal and Antioxidant Profile of Sheared and NonSheared Sheep - Khant, Malhar; Modi, Rakesh J; Patel, Nitin R; Wadhwani, Kishan N; Pathan, Mohsin M (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The effect of roofing material on hemato-biochemical, hormonal and antioxident parameters of sheared and non-sheared sheep wasinvastigated. Twenty four adult dry indigenous sheep were distributed randomly on the basis of body weight (20-35 kg) into two rooftreatment groups, i.e., T1: asbestos roof and T2: agronet roof. Each treatment comprised of six sheared and six non-sheared animals.Hemoglobin (g/dL) and PCV (%) concentrations of sheep were comparable between roof treatments and between shearing practices.Serum glucose level was significantly (p
Keywords: Blood biochemicals; HSP70; Roof type; Serum hormones; Shearing; Sheep